Economic Empowerment of Households through Financial Management Training in Ciputih Village - Amir Hamzah; Lia Dwi Martika; Oktaviani Rita Puspasari; Siti Nurfatimah (EQUATOR SINAR AKADEMIA, 2023)
Empowerment of Household Economics Through Financial Management Training in Ciputih Village is an effort to enhance household financial capabilities to drive economic stability and community resilience. Through tailored interactive workshops, the initiative introduced basic financial concepts, budget planning, savings, and investment strategies to the residents. Post-activity evaluations revealed improved financial understanding and better decision-making, evidenced by increased savings, enhanced budget allocation, and a heightened interest in entrepreneurship. The outcomes underscore the significance of financial education at the community level, strengthening not only individual aspects but also the overall village economy. Thus, empowerment through financial literacy aids not just households but also stimulates sustainable economic growth in rural communities.